Development And Validation Of A Service Quality Measurement Instrument For Cosmetic Retail Stores - Suryaneta, Suryaneta; Septiya Dewi, Kadek; Raufida, Nila; Ayu Swandari, Nimas; Rahmadani, Sinta; Noviantoro, Tri (Publisher Cv. Inara, 2025)
This study aimed to develop and validate a service quality measurement instrument specifically for brick-and-mortar cosmetic retail stores in Lampung Province, Indonesia. An initial pool of 40 items—reflecting six dimensions (store aesthetics, ambience, lighting, product display, store layout, and staff service quality)—was generated based on the literature and refined through expert review and pilot testing. Data were collected from 126 customers of three major cosmetic retailers in Lampung. Exploratory factor analysis (EFA) on 33 retained items revealed a stable three-factor structure (“Store Aesthetics,” “Ambience & Lighting,” and “Product Display, Layout & Staff Service”), explaining 70.6% of the total variance. Confirmatory factor analysis (CFA) confirmed model fit (CFI = 0.96; TLI = 0.95; RMSEA = 0.045; SRMR = 0.042). Each factor demonstrated high internal consistency (? ? 0.878; CR ? 0.90) and acceptable convergent validity (AVE ? 0.56) and discriminant validity. The final 26-item scale offers a psychometrically sound tool for assessing service quality in Indonesian cosmetic retail environments. Practically, managers can use this instrument to identify areas for improvement—in interior design, sensory ambience, merchandise presentation, store layout, and staff training—to enhance customer satisfaction and loyalty.